A STUDY ON HOME PURCHASE DECISIONS AMONG VIETNAMESE SPOUSES’ HOUSEHOLDS IN TAINAN - Chung Huang, Kan; Chin Lin, Linda Lin; Pin Chou, Kuei; Fang Zhuang, Shu; Hui Yang, Chiao (Graduate Program of Universitas Tarumanagara, 2025)
Previous research on households of new immigrant spouses in Taiwan has mainly focused on family upbringing and individual social adaptation. Studies such as Chen (2010), Liu et al. (2015), Chen et al. (2016), Wu & Tsai (2017), and Chen & Lin (2019) have highlighted the challenges and adaptations faced by new immigrant households under conditions of cultural differences and economic disadvantage. However, the crucial issue of housing remains underexplored. Moreover, existing housing policies and real estate market studies rarely reflect the real experiences of immigrant groups, especially the influence and agency of female immigrant spouses in household asset decisions. As Taiwan's demographic structure changes, new immigrants have become a significant group in housing demand, with Vietnamese spouses being the largest subgroup. This study aims to explore the motivations, information sources, cultural identities, and practical challenges of Vietnamese spouse households when purchasing homes. The findings contribute to filling the research gap and provide essential references for the design of multilingual and multicultural housing policies. This study focuses on Tainan City and adopts a qualitative research approach through in-depth interviews with eight Vietnamese spouses aged between 30 and 50 who have already purchased homes. The interviews covered their home-buying experiences, family role divisions, information acquisition methods, cultural values, and housing expectations. Thematic analysis was used to derive decision-making patterns and influencing factors in their home purchase behavior. Results show that home-buying motivations are closely linked to their Taiwanese spouses, primarily driven by the need for residential stability, children's education, and long-term settlement. Most prefer townhouses with spacious and multi-functional interiors. Although some new immigrants have basic knowledge of the real estate market, most still rely on their spouses or family for support, indicating limited access to market and policy information. Culturally, traditional Vietnamese family values and religious beliefs continue to influence housing decisions and spatial use.